2023
DOI: 10.18502/ijph.v52i3.12129
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients with Chronic Hepati-tis B: A Meta-Analysis of Observational Studies

Abstract: Background: Chronic hepatitis B virus (CHB) infection is one of the most common liver infections worldwide. Approximately 240 million patients are diagnosed with CHB. The objective of this meta-analysis was to identify the effect of CHB on the affected patients’ health-related quality of life and compare with the control group. Methods: A comprehensive search was conducted through PubMed, Medline, ProQuest, Cochrane Central Register of Controlled Trials, Clinicaltrials.gov, and Web of Science databases u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…As the condition worsens, it can lead to serious complications such as liver cirrhosis and liver cancer, which can endanger the patient's life. [1][2][3] It is reported that HBV infection is a global epidemic, and in recent years, with the influence of factors such as work and lifestyle habits, the incidence of HBV infection has continued to rise. If the disease is not controlled in a timely manner, it can be transmitted through blood, body fluids, and mother-to-child transmission.…”
Section: Introductionmentioning
confidence: 99%
“…As the condition worsens, it can lead to serious complications such as liver cirrhosis and liver cancer, which can endanger the patient's life. [1][2][3] It is reported that HBV infection is a global epidemic, and in recent years, with the influence of factors such as work and lifestyle habits, the incidence of HBV infection has continued to rise. If the disease is not controlled in a timely manner, it can be transmitted through blood, body fluids, and mother-to-child transmission.…”
Section: Introductionmentioning
confidence: 99%